Representing perpetrator trauma in Ian McEwan’s The Children Act - He, Qijia; Kaur, Hardev; Ujum, Diana Abu; Ching, Florence Toh Haw (Academy Publication, 2024)
The concept of trauma explains a disruptive experience with belated effects that are hardly controlled or mastered. Trauma damages one’s psychology by distorting the sense of self and the perception of the world. However, the application of conventional trauma theories focuses on the pains and sufferings in the victim’s life only. It has been critiqued the reluctance to acknowledge that hurting others may cause some perpetrators to experience psychological injuries as well. Drawing on Dominick LaCapra’s concepts of historical trauma and structural trauma, acting out and working through, as well as Judith Butler’s concepts of posttraumatic symptoms, which are described as vulnerability, grief and aggression, this study inquires into the traumatic experience of the protagonist Fiona Maye in Ian McEwan’s The Children Act. It aims to investigate how she transforms from a victim to a perpetrator within the context of trauma. Specifically, it explores how Fiona’s personal traumas happened earlier in life are reactivated and drive her to take the role of a perpetrator, and to hurt Adam Henry with her coldness and aggression that facilitates Adam’s death. Besides, the study also looks at how Fiona gets psychological injuries from her perpetrations. This study concludes that the perpetrator’s aggression in this situation serves as a method of self-protection and release of her repressed trauma, but traumatizing others can never be the antidote for her plights, and she is inevitably traumatized by scheming and carrying out the villainies that hurt others.